Alternativas técnico-metodológicas para a detecção de cetáceos durante atividades de prospecção sísmica - Silva, Letícia Aurora Coelho da (Brasil, 2019)
One of the most intense anthropogenic noises occurring in the oceans is caused by the use of air guns for seismic surveys. The highest energy levels produced by seismic surveys overlap the sound frequencies emitted by baleen whales, and most of their noise emissions are within the toothed whale's auditory range. Brazilian research should continue to contribute with scientific knowledge for the improvement of seismic surveys mitigation measures in our country and contribute with the development of cetacean detection techniques in the context of offshore seismic operations. The detection of cetaceans involves monitoring the oceans in two ways: a) visual monitoring; and b) passive acoustic monitoring (PAM). Were used as independent platforms of simultaneous monitoring, the seismic platform (seismic vessel) and the auxiliary platform (seismic auxiliary vessel). In the present study, the main objective is to compare technical-methodological alternatives for the detection of cetaceans during seismic surveys activities. The specific objectives are: a) to verify if there is a difference in the total number of visual detections per day between the platforms; b) to verify is there is a difference in the maximum value of acoustic detection per hour of recording between the platforms; and c) to verify if there is an association of visual detection of groups of cetaceans (baleen whales, toothed whales, large cetaceans and sperm whales) and acoustic detection of groups of cetaceans (baleen whales, toothed whales and sperm whales) with the monitoring platforms. During the 28 days of data collection, 68 sighting events (with 110 individuals sighted) were performed by the seismic platform and 70 sighting events (with 163 individuals sighted) were performed by the auxiliary platform. During the 10 days used for the statistical analysis of the acoustic data, 15 hours were used, as these are the hours that have corresponding hours recorded between the platforms. The auxiliary platform detected a total of 6422 acoustic cetacean ...